Analisis Kebutuhan Pengembangan Aplikasi M-Learning Berbasis Android pada Materi Jaringan Hewan - Arifuddin, Muh.; Bahri, Arsad (Universitas Negeri Makassar, 2019)
Abstract. Technological developments affect people's lifestyles. Including in high school students, currently many high school students have an Android-based mobile phone whose utilization is not maximal. The use of learning media is something that cannot be separated and is already an integration of the learning methods used, learning media can explain what the teacher is less able to say through words, so abstractness in a subject concept can be concretized. This study aims to determine the potential use of android-based learning media in the XI class of high school animal material. With the use of android students can repeat animal network material and students can better understand the concepts in learning, can repeat lessons that have not yet been understood as a result of lack of face-to-face time in class, and can also make students independent learning because of the availability of subject matter which can be accessed anywhere using Android. The results of this study indicate that the use of android in learning can attract students' interest and motivation in learning and also help students understand concepts in animal tissue material and can make students learn independently. The development of animation learning media that can be run on an Android-based device can increase the benefits of using Android-based devices and help the learning process of students using Android-based devices. This development and research use research and development design based on the ADDIE development model.Keywords: android application, learning media